A Single-Center 10-Year Experience with Pasireotide in Cushing’s Disease: Patients’ Characteristics and Outcome - Trementino, L.; Michetti, G.; Angeletti, A.; Marcelli, G.; Concettoni, C.; Cardinaletti, C.; Polenta, B.; Boscaro, M.; Arnaldi, G. (Hormone and Metabolic Research, 2016)
Pasireotide is the first pituitary-directed drug approved for treating patients with Cushing’s disease (CD). Our 10-year experience with pasireotide in CD is reported here. Twenty patients with de novo, persistent, or recurrent CD after pituitary surgery were treated with pasireotide from December 2003 to December 2014. Twelve patients were treated with pasireotide in randomized trials and 8 patients with pasireotide sc (Signifor®; Novartis AG, Basel, Switzerland) in clinical practice. The mean treatment duration was 20.5 months (median 9 months; range, 3–72 months). Urinary free cortisol (UFC) levels mean percentage change (± SD) at last follow-up was−40.4% (± 35.1; range, 2–92%; median reduction 33.3%) with a normalization rate of 50% (10/20). Ten patients achieved sustained normalized late night salivary cortisol (LNSC) levels during treatment. LNSC normalization was associated with UFC normalization in 7/10 patients. Serum cortisol and plasma ACTH significantly decreased from baseline to last follow-up. Body weight decrease and blood pressure improvement during pasireotide treatment were independent from UFC response. Glucose profile worsening was observed in all patients except one. The frequency of diabetes mellitus increased from 40% (8/20) at baseline to 85% (17/20) at last follow-up requiring initiation of medical treatment only in 44% of patients. Pasireotide treatment was associated with sustained biochemical and clinical benefit in about 60% of CD patients. Glucose profile alteration is a frequent complication of pasireotide treatment; however, it seems to be easy to manage with diet and lifestyle intervention in almost half of the patients.
Keywords: endogenous hypercortisolism; pituitary; somatostatin analogue; medical treatment; long-term